GENETIC ANALYSIS OF FEMALE FERTILITY HEALTH TRAITS IN KARAN FRIES (HOLSTEIN CROSSBRED) COWS - SHARMA, P C; GUPTA, A K; MOHANTY, T K; CHAKRAVARTY, A K; SINGH, A; SHARMA, A K; B, BALASUN0ARAM (The Indian Journal of Animal Reproduction, 2011)
A total of 2972 parity records on 977 Karan Fries (Holstein crossbred) cows were analyzed to assess the influence of genetic and non-genetic factors on indicators for fertility health traits. The proportion of overall incidence was estimated as 0.05 for repeat breeding and 0.20 for anestrus. The period and parity of calving had significant effect (P<0.01) on health indicator traits, w ile season and genetic group showed non-significant effect. The heritability was estimated as 0.26 for repeat breeding and 0.53 for anestrus in primiparous; 0.07 for repeat breeding and 0.19 for anestrus in pluriparous cows. The values of rank correlations among ranks of sires based on breeding value for repeat breeding and anestrus were found to be negative and high (P<0.001) for production traits and positive and moderate P<0.05) for reproduction traits except for first dry period (FOP.